(a x 1 - a : 1) : 8
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = \(\frac{1}{1.2.4}+\frac{1}{2.4.5}+...+\frac{1}{8.10.11}+\frac{1}{10.11.13}\)
3 x A = \(\frac{3}{1.2.4}+\frac{3}{2.4.5}+...+\frac{3}{8.10.11}+\frac{3}{10.11.13}\)
3 x A = \(\frac{1}{1.2}-\frac{1}{2.4}+\frac{1}{2.4}-\frac{1}{4.5}+...+\frac{1}{8.10}-\frac{1}{10.11}+\frac{1}{10.11}-\frac{1}{11.13}\)
3 x A = \(\frac{1}{1.2}-\frac{1}{11.13}=\frac{1}{2}-\frac{1}{143}=\frac{143}{286}-\frac{2}{286}=\frac{141}{286}\)
A = \(\frac{141}{286}:3=\frac{141}{286.3}=\frac{47}{286}\)
1)
=a^4+2a^2+1-a^2
=(a^2+1)^2-a^2
=(a^2-a+1)(a^2+a+1)
2)
=a^4+4b^4-4a^2b^2
=(a^2+2b^2)^2-4a^2b^2
=(a^2-2ab+2b^2)(a^2+2ab+2b^2)
3)
=(8x^2+1)^2-16x^2
=(8x^2-4x+1)(8x^2+4x+1).
4)
=x^5+x^4+x^3-x^3+1
=x^2(x^2+x+1)-(x-1)(x^2+x+1)
=(x^2-x+1)(x^2+x+1)
5).
=x^7-x+x^2+x+1
=x(x^6-1)+x^2+x+1
=x(x^3-1)(x^3+1)+x^2+x+1
=x(x-1)(x^2+x+1)(x^3+1)+x^2+x+1
=(x^2+x+1)[(x^2-x)(x^3+1)+1]
6)
=x^8-x^2+x^2+x+1
=x^2(x-1)(x^2+x+1)(x^3+1)+x^2+x+1
Xong nhóm x^2+x+1 vào.
7)
=x^4-(2x-1)^2
=(x^2-2x+1)(x^2+2x-1)
8)
=(a^8+b^8)^2-a^8b^8
=(a^8-a^4b^4+b^8)(a^8+a^4b^4+b^8).
ta có:\(A=\frac{8^9+12}{8^9+7}=\frac{8^9+7+5}{8^9+7}=\frac{8^9+7}{8^9+7}+\frac{5}{8^9+7}=1+\frac{5}{8^9+7}\)
\(B=\frac{8^{10}+4}{8^{10}-1}=\frac{8^{10}-1+5}{8^{10}-1}=\frac{8^{10}-1}{8^{10}-1}+\frac{5}{8^{10}-1}=1+\frac{5}{8^{10}-1}\)
vì 810-1>89+7
\(\Rightarrow\frac{5}{8^{10}-1}<\frac{5}{8^9+7}\)
\(\Rightarrow1+\frac{5}{8^{10}-1}<1+\frac{5}{8^9+7}\)
=>A<B
1, a4 + a2 + 1
= a4 + 2a2 + 1 - a2
= (a2)2 + 2a2 + 1 - a2
= (a2 + 1)2 - a2
= (a2 + 1 - a)(a2 + 1 + a)
2, a4 + 4b4
= (a2)2 + 2. a2 . b2 + (2b)2 - a2 . b2
= (a2 + 2b)2 - (ab)2
= (a2 + 2b - ab)(a2 + 2b + ab)
3, 64x4 + 1
= (8x2)2 + 16x2 + 1 - 16x2
= (8x2 + 1)2 - (4x)2
= (8x2 + 1 - 4x)(8x2 + 1 + 4x)
4, x5 + x4 + 1
= x5 + x4 + x3 - x3 - x2 - x + x + x2 + 1
= (x5 + x4 + x3) - (x3 + x2 + x) + (x + x2 + 1)
= x3(x2 + x + 1) - x(x2 + x + 1) + (x2 + x + 1)
= (x2 + x + 1)(x3 - x + 1)
5, x7 + x2 + 1
= x7 – x + x2 + x + 1
= x(x6 – 1) + (x2 + x + 1)
= x(x3 – 1)(x3 + 1) + (x2 + x + 1)
= x(x3 + 1)(x – 1) (x2 + x + 1) + (x2 + x + 1)
= (x2 + x + 1)[ x(x3 + 1)(x – 1) + 1]
= (x2 + x + 1)(x5 – x4 + x3 – x2 + x – 1)
6, x8 + x + 1
= x8 + x7 + x6 - x7 - x6 - x5 + x5 + x4 + x3 - x4 - x3 - x2 + x2 + x + 1
= (x8 + x7 + x6) - (x7 + x6 + x5) + (x5 + x4 + x3 ) - (x4 + x3 + x2) + (x2 + x + 1)
= x6(x2 + x + 1) - x5(x2 + x + 1) + x3(x2 + x + 1) - x2(x2 + x + 1) + (x2 + x + 1)
= (x2 + x + 1)(x6 - x5 + x3 - x2 + 1)
7, x4 - 4x2 + 4x - 1
= x4 - (4x2 - 4x + 1)
= (x2)2 - (2x - 1)2
= (x2 - 2x + 1)(x2 + 2x - 1)
= (x - 1)2 (x2 + 2x - 1)
8, a16 + a8b8 + b16
= (a16 + 2a8b8 + b16) - a8b8
= (a8 + b8)2 - (a4b4)2
= (a8 + b8 - a4b4)(a8 + b8 + a4b4)
= (a8 + b8 - a4b4)[(a8 + b8 + 2a4b4) - a4b4]
= (a8 + b8 - a4b4)[(a4 + b4)2 - (a2b2)2]
= (a8 + b8 - a4b4)(a4 + b4 - a2b2)(a4 + b4 + a2b2)
= (a8 + b8 - a4b4)(a4 + b4 - a2b2)[(a4 + b4 + 2a2b2) - a2b2]
= (a8 + b8 - a4b4)(a4 + b4 - a2b2)[(a2 + b2) - (ab)2]
= (a8 + b8 - a4b4)(a4 + b4 - a2b2)(a2 + b2 - ab)(a2 + b2 + ab)
Bài 5:
a: \(8A=8+8^2+...+8^8\)
\(\Leftrightarrow7A=8^8-1\)
hay \(A=\dfrac{8^8-1}{7}\)
b: \(8B=\left(3^2-1\right)\left(3^2+1\right)\left(3^4+1\right)\left(3^8+1\right)\)
\(\Leftrightarrow8B=\left(3^4-1\right)\left(3^4+1\right)\left(3^8+1\right)\)
\(\Leftrightarrow8B=3^{16}-1\)
hay \(B=\dfrac{3^{16}-1}{8}\)
Áp dụng BĐT phụ \(a^2+b^2\ge\dfrac{1}{2}\left(a+b\right)^2\Leftrightarrow\left(a-b\right)^2\ge0\)
\(A\ge\dfrac{1}{2}\left(x+y+\dfrac{1}{x}+\dfrac{1}{y}\right)^2\ge\dfrac{1}{2}\left(x+y+\dfrac{4}{x+y}\right)^2=\dfrac{1}{2}\left(1+\dfrac{4}{1}\right)^2=\dfrac{25}{2}\)
Dấu "=" \(x=y=\dfrac{1}{2}\)
(a x 1 - a : 1) : 8 = (a - a) : 8 = 0 : 8 = 0